An Intuitive Logical Woman: Personality of Main Female Character in “Arrival” Movie by Eric Heisserer - Destoprani Brajannoto; Yumna Rasyid; Ninuk Lustyantie (Bina Nusantara University, 2018)
This research examined the main female character in the movie